2008
DOI: 10.3390/s8084961
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Sensors Based on Cyclodextrin Derivatives

Abstract: This review focuses on chemical sensors based on cyclodextrin (CD) derivatives. This has been a field of classical interest, and is now of current interest for numerous scientists. First, typical chemical sensors using chromophore appended CDs are mentioned. Various “turn-off” and “turn-on” fluorescent chemical sensors, in which fluorescence intensity was decreased or increased by complexation with guest molecules, respectively, were synthesized. Dye modified CDs and photoactive metal ion-ligand complex append… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
169
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(170 citation statements)
references
References 93 publications
1
169
0
Order By: Relevance
“…(24) Cyclodextrins (CDs) are cyclic oligomers and calixarenes (CXs) are groups of cyclic macromolecules, both of which can form inclusion complexes with organic molecules in their hydrophobic cavities, which are available in different sizes. (25)(26)(27) The chemical structures of the ionophores used in this study are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…(24) Cyclodextrins (CDs) are cyclic oligomers and calixarenes (CXs) are groups of cyclic macromolecules, both of which can form inclusion complexes with organic molecules in their hydrophobic cavities, which are available in different sizes. (25)(26)(27) The chemical structures of the ionophores used in this study are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its structural properties, cyclodextrin continues to be one of the most studied host molecules, and has found application in various fields such as drug delivery 1,2 and stimulus sensing. 3 Cyclodextrins are cyclic oligosaccharides consisting of six, seven, or eight glucose units joined by α-1,4-linkages, termed α, β, and γ-cyclodextrin, respectively. The molecules are identical in height but vary in diameter and volume based on unit number.…”
Section: Introductionmentioning
confidence: 99%
“…The cavity diameter of CDs is about 0.44 -0.83 nm ( -CD: 0.49 nm, -CD: 0.62 nm, -CD: 0.80 nm) [7,8]. Furthermore, recent novel approaches to chemical sensing systems using supramolecular structures such as CD dimers, trimers and cooperative binding systems of CDs with the other supramoleculars have been mentioned [9]. When a competitive guest is added to the aqueous solution of fluorophore-CD, the fluorophore is excluded from the inside to the outside of the CD cavity.…”
Section: Cyclodextrins (Cds)mentioning
confidence: 99%